Evaluation of Terminalia Chebula Retz. Extract as a Natural Preservative for Cosmetic Products - Panichkul, Tassanee; Prompamorn, Piyanuch; Itsarasook, Khwunjit; Chantree, Kanlayaporn; Modsuwan, Jarasfah; Tanghiranrat , Jittarawadee (Burapha Science Journal, 2026)
The objective of this study was to evaluate the efficiency of Terminalia chebula Retz. fruit extract as a natural preservative in topical cream formulation. The antimicrobial activity of T. chebula Retz. extract against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans was determined by agar well diffusion assay and broth microdilution assay. The result showed that T. chebula Retz. extract exhibited a strong antimicrobial activity against all tested microorganisms. The minimal concentration of extract inhibited 50% of microbial growth (MIC50) were 0.22±0.05 to 0.68± 0.11 mg/ml. This extract could kill these microorganisms as shown with minimal bactericidal/fungicidal concentration (MBC/MFC) of 5-20 mg/ml. After that, T. chebula Retz. extract used as a preservative in topical cream was evaluated the antimicrobial effectiveness by challenge test method according to a criteria A of ISO 11930. Results showed that criteria A for bacterial inhibitory activity of T. chebula Retz. extract was fulfilled for preservative in cosmetic formulation but fungal inhibitory activity of this extract was below the acceptance value of criteria A. This study exhibited that T. chebula Retz. extract acts as a natural preservative for bacterial inhibition, or will be applied in combined with synthetic preservatives in cosmetic products.